Changes in the Eradication Efficacy of Fluoroquinolone-containing Triple Therapy for Infection in Korea - Jung Won Lee; Nayoung Kim; Geun Kim; Siho Kim; Hwawon Nam; Siwon Lee; Cheol Min Shin; Young Soo Park; Dong Ho Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims Fluoroquinolone-containing triple eradication therapy could be considered an alternative regimen for the second- line treatment of Helicobacter pylori infection. This study aimed to investigate the changes in the eradication efficacy of fluoroquinolone- containing triple therapy from 2003 to 2018 in Korea.Materials and Methods Patients with a history of first-line eradication therapy failure were consecutively enrolled at Seoul National University Bundang Hospital from 2003 to 2018. All patients took moxifloxacin-containing triple therapy as the second-line eradication therapy. The treatment regimen comprised a three-drug combination comprising a proton pump inhibitor, amoxicillin, and moxifloxacin. Data on age, sex, endoscopic diagnosis, eradication results, compliance, and adverse outcomes were acquired and analyzed. Results In total, 824 participants were enrolled during the study period, of whom, 46 were lost to follow-up. Finally, 778 participants were included in the per-protocol (PP) analysis, of whom, 72.1% received moxifloxacin-containing triple therapy for 14 days. The eradication rate of moxifloxacin-containing triple therapy was 72.1% (594/824) in the intention-to-treat analysis and 76.3% (594/778) in the PP analysis. A decline in eradication efficacy was observed, especially in the PP analysis (P=0.046). Diarrhea was the most commonly observed adverse event, accounting for 19.6% (41/209) of recorded adverse events. Conclusions Moxifloxacin-containing triple therapy has shown suboptimal eradication efficacy as the second-line eradication therapy. In addition, there is a concern that eradication rate will decrease due to increase in antimicrobial resistance.